Integrating Themes of Care into English Curriculum: Toward the Enhancement of Students’ Moral Reasoning Skill - Sugiono, Sugiono (Universitas Nurul Jadid, 2021)
The purpose of the study is to explore possible strategies to ‘insert’ themes of care into Indonesia’s English curriculum. It is stipulated that the English curriculum containing themes of care, ethics and morality can contribute to the advancement of students’ engagement in learning and enable moral reasoning skill toward the generation of responsible members of society upholding values of tolerance and respect for difference of others. This is a library research, employing a qualitative content review of related literature to find strategies for integrating themes of care into English curriculum. It is found that integrating themes of care into curricular subjects, including English, is very possible to undertake, and provides students with higher order thinking skills in a functional manner. It is of great importance to students as they get benefits from being taught the ways to approach and eventually solve complex, real-life moral problems by applying particular skills drawn from the PAVE moral reasoning strategy. The English curriculum addressing such a long-term outcome for the application of the integration incorporates teaching students how to attain balanced competence, academically, socially and morally all at once.